2020
DOI: 10.9734/ejnfs/2020/v12i430215
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antioxidant Activities of Hydroethanolic Extract of Defatted Wonderful Kola (Buchholzia coriacea) Seeds and Its Safety Evaluation in Murine Models

Abstract: Introduction: Buccholzia coriaceaseed possesses a vast number of therapeutic applications in African traditional medicine. However, there are still limited information on its bioactive constituents, pharmacological actions and safety profile. This study was designed to prepare hydroethanolic extract of (defatted) Buccholzia coriacea seeds (HEBCS), evaluate its total phenols and flavonoids, in vitro antioxidant activity and its safety in rats and mice. Methods: Seeds were defatted with hexane and the resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Studies have shown that Buchholzia coriacea possesses medicinal properties that can be used as antimicrobial, anthelmintic, anti-trypanosomal, hypoglycaemic, and analgesic [2]. The plant has been widely investigated due to its several medicinal properties [3,4]. The antimicrobial properties of the Buchholzia coriacea seed have been reported by Ezekiel and Onyeoziri [5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Buchholzia coriacea possesses medicinal properties that can be used as antimicrobial, anthelmintic, anti-trypanosomal, hypoglycaemic, and analgesic [2]. The plant has been widely investigated due to its several medicinal properties [3,4]. The antimicrobial properties of the Buchholzia coriacea seed have been reported by Ezekiel and Onyeoziri [5].…”
Section: Introductionmentioning
confidence: 99%